2018
DOI: 10.1002/slct.201801204
|View full text |Cite
|
Sign up to set email alerts
|

4′‐Phenyl‐2,2′:6′,2′′‐terpyridine Derivatives Containing 1‐Substituted‐2,3‐Triazole Ring: Synthesis, Characterization and Anticancer Activity

Abstract: Terpyridine moiety is known for chelating and interesting physicochemical properties enabling some applications. Its biological activity, particularly anticancer potency is not well studied. Herein we present six 4′‐(1‐substituted‐2,3‐triazol‐4‐yl)phenyl‐2,2′:6′,2′′‐terpyridine derivatives with glycidyl, cyclohexylmethyl, benzyl, 4‐tert‐butylbenzyl, pentafluorobenzyl, and 2,6‐dichlorobenzyl groups which were obtained via Cu(I)‐catalysed 1,3‐dipolar cycloaddition reaction. The photophysical such as optical (abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…It appears that this signal may come from the cell nucleus. Similar co-localization studies may support this hypothesis for terpyridine containing dichlorophenol substituent or 1,8naphalimide derivatives, which nucleus-targeted imaging [56,57]. In summary, the tested 3-imino-1,8-naphatalimides may be interesting imaging tools and fluorescent materials for diagnostic applications and molecular bioimaging.…”
Section: Cell Imagingsupporting
confidence: 67%
“…It appears that this signal may come from the cell nucleus. Similar co-localization studies may support this hypothesis for terpyridine containing dichlorophenol substituent or 1,8naphalimide derivatives, which nucleus-targeted imaging [56,57]. In summary, the tested 3-imino-1,8-naphatalimides may be interesting imaging tools and fluorescent materials for diagnostic applications and molecular bioimaging.…”
Section: Cell Imagingsupporting
confidence: 67%
“…Cell cycle blockade during the G1 or S phases is more typical for the ligands while a higher concentration of uncoiled DNA during the phases S-M makes the cell more vulnerable to complexes with transition metals from the second or third row. These findings helped us design novel highly active Tpy derivatives oriented towards their potential cellular targets [ 78 , 79 , 80 ]. The most effective compounds reached nanomolar levels of activity with good selectivity.…”
Section: Should We Have Complexes With Terpyridines?mentioning
confidence: 99%
“…A number of systematic studies have been reported on the photophysical properties of 2,2 0 :6 0 ,2 00 -terpyridine derivatives with different aromatic peripheral substituents. Although the presence of a 1,2,3-triazole group in the terpyridine skeleton has been rarely introduced, 21 it can infer an important effect on the optical properties of the terpyridine derivatives and thus their application in optoelectronics and medicine. The photophysical and electronic properties of 3A1-3A7 in a chloroform solution were studied by UV-Vis and uorescence (PL) spectroscopy to investigate the relation between the character of the substituted triazole unit in 3A1-3A7 and the photophysical behaviour of these compounds.…”
Section: Uv-vis Absorption Photoluminescence and Td-dft Studymentioning
confidence: 99%
“…19,20 As abovementioned, we have already presented the preparation of a series of 4 0 -(1-substituted-2,3-triazol-4-yl)phenyl-2,2 0 :6 0 ,2 00 -terpyridine derivatives and investigation of their photophysical and thermal properties and antiproliferative activity. 21 We have found that in the case of the (1-substituted)-2,3-triazol-4-yl ring, the change in the substituents has an insignicant effect on its photophysical properties, and identical maxima of absorption and emission and values of lifetime have been observed; however, the quantum yields are different. Moreover, biological studies conducted on a panel of cancer cells showed that the studied compounds exhibited good anticancer activity at the nanomolar level with a good selectivity index, and the mechanism of action could be described as the interaction of these compounds with the DNA of cells.…”
mentioning
confidence: 94%